Flexible wire for supplying to thermal spray torch and thermal spray device
By using the wire composed of wire -shaped core and protective cover as a thermal spraying, it solves the problem of suspension stability and energy efficiency, and realizes the production of high -quality coating and the continuous material of the torch.
Patent Information
- Application Number
- CN202380046835.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-04
- Filing Date
- 2023-05-04
- Publication Date
- 2025-01-24
AI Technical Summary
In the existing thermal spraying technology, the use of suspension or liquid solution as feeding media has problems of stability and repeatability, and the evaporation of the solvent affects the energy efficiency, making it difficult to prepare a stable suspension, especially when containing particles of different compositions. .
The lines consisting of a condoms covered by the wire and the length of the core in the form of silk are used as a feed medium. The core consists of inorganic particles and polymer adhesives with a medium -value particle size of less than 10 microns. The equivalent outer diameter of the line is between 1mm and 3.5mm.
Realize the continuous and reliable feed of the torch, produce high -quality coating, improve the stability and energy efficiency of the method, and reduce the impact of particle node blocks and solvents evaporation.
Smart Images

Figure CN119365625A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a flexible cord for use as feedstock for a thermal spray torch to produce a coating. The invention also relates to a method of manufacturing the cord and a thermal spraying device using the cord. Background Art
[0002] Thermal spraying technology consists in using a heat source and kinetic energy to melt a collection of inorganic particles (initially in the form of wires or powders) and to eject at least partially molten particles onto a substrate. After impact, the at least partially molten particles spread out on the substrate and cool. Thus, these particles can effectively adhere to each other and to the substrate as they cool, and form a coating.
[0003] There are a variety of techniques, which can be divided into the following categories: "combustion enthalpy", "discharge" and "momentum density".
[0004] The category of "combustion enthalpy" includes the "detonation gun" and "powder flame" techniques (producing particle velocities <80 m / s, only powders can be used as feedstock), the "wire flame" technique (producing particle velocities >150 m / s, being able to use a medium selected from wires, wires or rods as feedstock), and finally the "high-speed flame" technique (producing particle velocities >500 m / s). Within the "high-speed flame" techniques, a distinction can be made between the "D-gun detonation", "HVOF" (high-speed oxygen fuel), "HVSFS" (high-speed suspension flame) and "HVAF" (high-speed air fuel) techniques, which are able to use powders, suspensions (in the case of HVSFS) or even wires as feedstock.
[0005] The “discharge” category includes both “arc” and “plasma” techniques, the latter including methods known as “atmospheric” or APS (atmospheric plasma spray), methods carried out in a controlled atmosphere and temperature, such as “VPS / LPPS” (vacuum or low pressure plasma spray), “VLPPS / PS-PVD” (very low pressure plasma spray and plasma spray enhanced physical vapor deposition), “SPS” (suspension plasma spray), “SPPS” (solution precursor plasma spray), “induction plasma” and “WSP” (water stabilized plasma) techniques. These systems enable particles to be propelled at speeds ranging from 150 m / s to 500 m / s, depending on the method variant and parameters adopted. These “plasma” systems can be used with median particle sizes D 50 Dry powders, or liquids (chemical precursors, such as salts, or containing median particle size D50 suspension of inorganic particles smaller than 10 microns).
[0006] The “momentum density” category includes the “cold spray” technology, which includes the “low pressure,” “high pressure,” and “recirculating helium” technologies.
[0007] All these techniques are known and are described, inter alia, in the book “ASM Handbook vol 5a Thermal Spray Technology”.
[0008] Each technology is associated with its own specific limitations, so the problems encountered and the solutions adopted to overcome them usually differ depending on the technology considered.
[0009] The present invention particularly relates to the grouping of the following subsets:
[0010] - in the category "Enthalpy of Combustion", "flame-wire" and "high velocity flame" techniques; and
[0011] - Technologies from the "discharge" category, in particular "plasma" technologies.
[0012] For the sake of clarity, in this specification, the torches or guns used in these techniques are generally referred to as "torches". The term "torch" particularly includes flame guns of the wire flame (WFS or wire flame spray) type, or plasma torch systems, or finally "high-speed flame spray" devices as described above. The latest developments in these technologies are to use suspensions or solutions of liquid precursors as feedstock in these devices (the suspension consists of a solvent and a median particle size D 50 The invention relates to the process of preparing a spraying agent, which is a kind of dispersion medium, and the dispersion medium is a kind of dispersion medium. The dispersion medium is composed of fine inorganic particles, which are usually less than 5 microns. This progress towards very fine particles (or even in the case of liquid precursors, in situ forming materials) has enabled the production of new types of microstructures, such as very finely structured, very dense, or columnar or "feathery" microstructures (having the appearance of feather juxtaposition when observed in a microphotographic cross section). These advances have opened up new prospects, but have encountered constraints and limitations on the robustness, stability and repeatability of the methods, which are related to the fact that the particle suspension is not always completely stable. However, the evaporation of the solvent is detrimental to the energy efficiency during the spraying stage. In addition, when the suspension contains particles of different compositions, in particular particles of different densities, the preparation of such a stable suspension (without any settling or agglomeration of the particles) is difficult or even impossible to control on an industrial scale.
[0013] JP2016156058A describes a feed medium consisting of composite filaments. The coating is a dense electrolytic membrane used to make fuel cells. Such filaments are difficult to manufacture and do not allow the production of ceramic (e.g. oxide) coatings with good control over the sprayed particle size. In particular, the medium includes fine particles embedded in a matrix. Tests have shown that a large amount of matrix leads to a detrimental enthalpy change during the spraying process.
[0014] US 4 593 856 also describes a feed medium in the form of a wire. However, the melting of the wire may be incomplete, which is detrimental to the quality of the coating.
[0015] Wires comprising a core coated with a sheath are known as feedstock for welding torches for applying thick layers metallurgically bonded to a metallic support (welding or hardfacing). They are not suitable for producing coatings by thermal spraying, which can be applied without resorting to a welding step and which can consist of ceramic and be applied to any type of support. These wires for welding consist of inorganic particles having a size greater than 10 micrometers.
[0016] An arc welding wire is also known from US 3 701 444. Such a wire is not usually used as feedstock for thermal spraying torches to produce coatings, since the two applications (welding / spraying) are very different from each other. In particular, the aggregates of inorganic particles usually have a median diameter greater than or equal to 100 micrometers.
[0017] FR 1 443 142 finally describes a thread comprising a core coated with a sheath. The aggregate of inorganic particles has a median particle size D which is incompatible with obtaining a highly uniform or finely structured coating. 50 .
[0018] Therefore, there is a continuing need for feed media suitable for spraying using plasma or flame torches that:
[0019] - allows the torch to be fed substantially continuously and reliably,
[0020] - the ability to overcome the constraints and limitations of liquid suspension or liquid solution type media, in particular by having the media in a solid, stable, easily manipulable form, preferably capable of being wound on a reel;
[0021] - Produce highly uniform or finely structured coatings;
[0022] - The torch is not excessively worn; and
[0023] - At the expense of limited energy consumption.
[0024] The present invention seeks to at least partially meet this need. Summary of the invention
[0025] According to the invention, this object is achieved by a wire having an equivalent outer diameter of 1 to 3.5 mm and consisting of a core or "central part" in the form of a wire and a sheath covering the core along its entire length,
[0026] The core consists of:
[0027] -Median particle size D 50 an aggregate of inorganic particles smaller than 10 microns, the inorganic particles occupying greater than 40% and less than 80% of the volume of the core; and
[0028] - a matrix binding the inorganic particles, the matrix comprising a polymer binder and optionally a matrix lubricant, such as glycerol, the polymer binder and the optional matrix lubricant together accounting for more than 90% of the volume of the matrix, up to 100% of the supplement being able to consist of impurities;
[0029] The sheath has a thickness of 50 microns to 500 microns and comprises a sheath polymer and preferably a sheath lubricant (same or different from the optional base lubricant), the sheath polymer and preferably the sheath lubricant together accounting for greater than 90% to 100% of the volume of the sheath, the supplement preferably consisting of impurities and possible colorant pigments,
[0030] The volume percentages are determined without taking into account any solvent residues that may be present.
[0031] Surprisingly, the inventors have found that the wire according to the invention allows a torch to be fed continuously and reliably while producing high quality coatings, offering a number of advantages over the use of fine particle suspensions:
[0032] - The process is more stable, eliminating the problems associated with the stability of particle suspensions (risk of sedimentation, clumping);
[0033] - Lower energy consumption due to the absence of evaporation of the aqueous solvent used in the suspension;
[0034] - There is no agglomeration of particles at the injection point or in flight, unlike what is observed during thermal spraying of suspensions;
[0035] - Better control of the flow rate of the inorganic material, advantageously proportional to the speed of the line feed into the spraying device, whereas the injection of the suspension results in a significant variation of this flow rate.
[0036] Furthermore, feed media in the form of threads advantageously contain much less solvent than suspensions. The low solvent (especially water) content of threads (typically less than 5 mass%) greatly limits energy losses in thermal spraying of media intended to fully or partially melt the inorganic particles.
[0037] Without being bound by this theory, the inventors ultimately found that the characteristics of the wire resulted in only a small enthalpy change when sprayed. Therefore, the enthalpy change has a much smaller destructive effect on the thermal spray process than in the spraying of dry powders and using wires of the prior art. In particular, the inventors found that the combination of a core and a sheath containing a relatively low matrix content allows for a more reliable enthalpy change than a composite wire without a sheath and with a higher matrix content as in JP2016156058A. In general, the presence of a minimum amount of polymer is necessary, particularly in order to impart the desired flexibility, and the inventors found that increasing the concentration of inorganic particles in the core of the wire and adding a sheath to maintain this flexibility is preferred over a lower concentration of inorganic particles in the composite wire.
[0038] In a particularly advantageous embodiment, the ratio R of the equivalent outer diameter of the wire (in micrometers) to the median particle size of the aggregate of inorganic particles (in micrometers) is between 200 and 20000, preferably between 200 and 1600. It is worth noting that this configuration (in connection with the following: the volume content of inorganic particles relative to the volume of the core of the wire is greater than 40%, preferably greater than 50%, or even greater than 60%, and less than 80%, preferably less than 78%, preferably less than 75%) allows better dispersion of the particles when they are discharged in the plasma jet or flame after the decomposition of the sheath. This improvement in dispersion is particularly advantageous for high-speed plasma torches or flame torches, in particular torches with axial injection.
[0039] This results in a better compromise between the following properties and characteristics:
[0040] - when the wire is used in a thermal spraying process, optimal dispersion of the inorganic particles in the spray jet, without compacting the inorganic particles together, so that a coating with a fine microstructure can be obtained;
[0041] -Flexibility of the thread, making it easy to manipulate without risk of breaking;
[0042] - Low enthalpy required to decompose organic compounds and convert them into non-toxic gases.
[0043] The thread according to the invention may also include one or more of the following optional and preferred features:
[0044] - the combined entity of matrix and sheath of the thread has an ash content of less than 5%, preferably less than 3%, expressed as a percentage by mass based on the dry mass of the thread;
[0045] -Median particle size D of inorganic particle aggregate 50 Less than 5 microns, preferably less than 4 microns, preferably less than 3 microns, preferably less than 1 micron, especially to form a columnar structure;
[0046] - At 20°C, the viscosity of the core polymer binder and / or the sheath polymer and / or the material constituting the core and / or the material constituting the sheath is 30 mPa·s to 300 mPa·s, or 30 centipoise to 300 centipoise, the viscosity being The viscometer is measured on a mixture containing 2% by mass of dry powders of the core polymer binder and / or the sheath polymer and / or the material constituting the core and / or the material constituting the sheath, respectively, in demineralized water;
[0047] - the sheath and / or the matrix are made of a cellulose derivative, that is to say a component containing cellulose molecules, preferably methylhydroxyethylcellulose, a cellulose derivative having a viscosity particularly suitable for thermal spraying and an associated low ash content;
[0048] - Excluding any potential solvent, the inorganic particles account for more than 45%, preferably more than 50% and / or preferably less than 70%, preferably less than 75%, by volume percentage based on the volume of the core of the thread;
[0049] -Inorganic particles are:
[0050] - particles of one or more metal oxides, preferably particles of aluminum oxide, zirconium oxide, titanium oxide, chromium oxide, yttrium oxide, or a combination of several of these oxides, such as mullite or spinel, and / or
[0051] - particles of a cermet based on carbides, which can be, for example, carbides of chromium and / or tungsten and / or titanium and / or tantalum and / or zirconium and / or niobium, which are associated with a metal phase, and / or
[0052] - Inorganic particles containing SiC and YAG (yttrium-aluminum garnet) phases, allowing thermal spraying of SiC-based compounds;
[0053] - ceramic particles, preferably chosen from nitrides, borides or carbonitrides, which may be associated with the metal phase in the form of a cermet;
[0054] - particles made of refractory metal or refractory metal alloy, preferably with a melting point above 2500K;
[0055] - particles made of a special metal, preferably selected from amorphous metals, quasicrystals or quasicrystal approximants, more generally non-drawable metal alloys;
[0056] - particles preferably made of a brittle material, preferably a brittle metal or an alloy of a brittle metal;
[0057] - Inorganic particles are selected from particles made of ceramics, particles made of metal alloys, particles made of amorphous metals, particles made of quasicrystals or quasicrystal-like phases;
[0058] - the thickness of the sheath is greater than 100 microns, preferably greater than 150 microns and preferably less than 400 microns;
[0059] - For wires with an outer diameter of 2.5 mm to 3.5 mm, the thickness of the sheath is 200 microns to 400 microns;
[0060] - For wires with an outer diameter of 1 mm to 2.5 mm, the thickness of the sheath is 100 microns to 250 microns;
[0061] - the ash content of the thread is less than 2.5%, preferably less than 2%, preferably less than 1%, preferably less than 0.7%, preferably less than 0.5%, measured as a percentage by mass based on the dry mass of the thread;
[0062] - the polymer binder and the optional matrix lubricant (same or different from the lubricant of the sheath) together represent more than 95%, preferably more than 97%, preferably more than 99%, preferably substantially 100%, measured by volume percentage based on the volume of the matrix, without taking into account any solvent residues;
[0063] - the polymer binder (preferably a cellulose derivative, more preferably methylhydroxyethylcellulose) represents more than 5%, preferably more than 10% and / or less than 25%, preferably less than 20%, or even less than 15%, measured by volume percentage based on the volume of the core of the thread, without taking into account any solvent residues;
[0064] - in percentage by volume based on the volume of the core of the thread, without taking into account any solvent residues, the matrix preferably accounts for more than 25%, preferably more than 30%, preferably more than 40%, or even more than 45% and / or preferably less than 70%, preferably less than 60%, preferably less than 55%, preferably less than 50%;
[0065] - in one embodiment, the matrix comprises a matrix lubricant, the content of which, measured by volume percentage based on the volume of the core of the thread, without taking into account possible solvent residues, is greater than 5%, greater than 10% and / or less than 25%, or less than 20%;
[0066] - the base lubricant is selected from polyols, glycerides, in particular glycerol and its derivatives, stearates, amino alcohols, preferably selected from glycerin and triethanolamine, more preferably glycerol;
[0067] - the solvent of the matrix is water or denatured alcohol, preferably water;
[0068] - the residual solvent (preferably water) content in the core is less than 5% by mass based on the dry mass of the core of the thread;
[0069] - more than 99%, preferably substantially 100%, of the matrix consists of organic material, the percentages being by volume;
[0070] - in percentage by volume based on the volume of the sheath, not taking into account any solvent residues, the sheath polymer and the optional sheath lubricant together account for more than 95%, preferably more than 97%, preferably more than 99%, preferably substantially 100%;
[0071] The sheath contains a sheath lubricant (which may be the same as or different from the optional base lubricant) and the sheath lubricant content, measured as a percentage by volume based on the volume of the sheath, without taking into account any solvent residues that may be present, is greater than 10%, preferably greater than 20%, preferably greater than 30% and / or less than 50%, preferably less than 40%;
[0072] - a content of the sheath polymer of greater than 45%, preferably greater than 55%, preferably greater than 60% and / or preferably less than 80%, preferably less than 75%, preferably less than 70%, expressed as percentage by volume based on the volume of the sheath, without taking into account any solvent residues;
[0073] - the polymer binder and the sheathing polymer comprise the same polymer, preferably comprise only the same polymer as polymer, and preferably comprise the same polymer in the same proportions;
[0074] More than 90%, preferably more than 95%, preferably substantially 100% of the impurities in the matrix and / or the sheath consist of organic impurities and / or impurities containing the element hydrogen H and / or metallic impurities;
[0075] - the impurities in the matrix and / or the sheath account for less than 5%, preferably less than 3%, preferably less than 1%, respectively, in volume percentage based on the volume of the matrix and / or the sheath, without taking into account any solvent residues;
[0076] - the sheath comprises a colorant pigment, which may be any colorant conventionally used, which accounts for less than 1%, preferably less than 0.5%, preferably less than 0.4%, preferably less than 0.1%, or even less than 0.05% by volume of the sheath;
[0077] - the solvent of the sheath is preferably water or denatured alcohol, preferably water;
[0078] - the residual solvent (preferably water) content in the sheath is less than 10%, preferably less than 5%, as a percentage by mass based on the mass of the sheath of the thread;
[0079] - more than 99%, preferably substantially 100%, of the sheath consists of organic material, the percentages being by volume;
[0080] - The wire is wound on itself in the form of a roll or reel, preferably on a spool having a diameter greater than 50 mm, preferably greater than 100 mm, preferably greater than 150 mm, or even greater than 200 mm and / or less than 1000 mm, preferably less than 500 mm, preferably less than 400 mm, preferably less than 300 mm.
[0081] The wire according to the invention is not used for welding. Preferably, the wire does not contain any flux, which is an agent usually used for cleaning and deoxidation of the weld zone or forming a protective slag.
[0082] Preferably, the wire according to the invention does not contain any flux selected from fluorite or calcium fluoride, cryolite (which is a fluoride of aluminium oxide and sodium) and borates.
[0083] The present invention also relates to a thermal spraying device, comprising:
[0084] - a torch comprising a plasma generator or a flame generator and an injection device; and
[0085] - a wire according to the invention, arranged in such a way that it can be injected by injection means into the plasma or flame generated by said generator,
[0086] The torch is capable of at least partially melting the inorganic particles of the wire and ejecting the at least partially molten inorganic particles, preferably at a velocity exceeding 150 m / s.
[0087] The torch is preferably capable of ejecting at least partially molten inorganic particles at a speed of more than 150 m / s and / or less than 1000 m / s, the ejection speed being typically measured at the exit of the torch. In one embodiment, the particles are ejected at more than 300 m / s, preferably more than 500 m / s, preferably more than 600 m / s, preferably more than 700 m / s. In one embodiment, the particles are ejected at more than 150 m / s and less than 300 m / s.
[0088] The injection means are preferably arranged in such a way that the injection line is injected along an injection axis extending in a radial plane through the axis X of the plasma stream or flame and forming an angle θ with a plane P transverse to the axis X, the absolute value of which is greater than 60°, greater than 70°, greater than 80°, preferably greater than 85°, the injection axis I being preferably substantially parallel to the axis X, the injection or "feeding" of the feed being identified as "axial" injection or feeding. The torch is preferably an axially fed torch.
[0089] An angle θ close to 90° advantageously promotes uniform combustion of the sheath and the matrix, and thus uniform dispersion of the inorganic particles released at high speed into the plasma stream or flame. This makes it possible to ensure a centered and optimal path of the particles in the injection nozzle of the torch and reduces the risk of fouling of the injection nozzle, thereby reducing the risk of process failure and coating defects.
[0090] Preferably, the injection is carried out upstream of the injection nozzle through which the stream or "jet" of plasma or flame (in the case of a flame torch) flows. Preferably, for a flame torch, the wire is driven to the combustion chamber. Preferably, for a plasma torch (which is preferably a multi-cathode torch that injects the material to be sprayed axially), the wire is driven to the confluence zone of the elementary streams of plasma emanating from the cathodes, which confluence zone is upstream of the injection nozzle through which the jet of plasma resulting from the merging of these two elementary streams of plasma flows.
[0091] It is noteworthy that the wire according to the invention is flexible enough so that it can be spooled and unspooled, while being rigid enough to allow axial injection, preferably using conventional drive means located at the rear (upstream) of the torch.
[0092] The injection means preferably opens into the interior of the torch.
[0093] like Figure 1 As shown, the injection device is preferably arranged in such a way that the wire is introduced into the plasma chamber or combustion chamber 17, preferably into a portion 2 of the plasma flow or flame, which portion 2 extends from one or more orifices 7 through which the plasma flow or flame leaves the generator by less than 10 cm, preferably less than 5 cm and / or more than 2 cm, preferably more than 3 cm.
[0094] The torch may in particular be an axial injection multi-cathode plasma torch, or a high velocity flame torch of the HVOF or HVAF type, or a conventional wire flame torch, or a HVOF wire type torch or a HVAF wire type torch.
[0095] The invention also relates to a method for coating the surface of a substrate with a coating, in which method a wire according to the invention is injected into a plasma stream or flame from a torch so that inorganic particles of the wire, which are at least partially melted in the plasma stream or flame, are ejected onto the surface.
[0096] The invention finally relates to a method for thermal spraying by means of a thermal spraying device according to the invention, in which method a wire according to the invention is fed to a torch in order to form a coating on the surface of a substrate.
[0097] The substrate is preferably a substrate made of metal, ceramic, cermet, polymer, organic material or a composite material, preferably a substrate having a ceramic matrix.
[0098] The substrate can present different shapes, for example with a planar geometry or a rotational geometry, in particular a cylindrical geometry, or a complex geometry, the only limitation being the accessibility of the jet of at least partially molten inorganic particles. Axial feeding upstream of the spraying or jetting nozzle advantageously improves this accessibility.
[0099] In one embodiment, the coating provides surface functionality to the substrate, preferably improving wear resistance, modifying the coefficient of friction, or forming a thermal or electrical insulating barrier.
[0100] The coating can be used in particular to provide thermal, chemical or mechanical protection to components, in particular in reactors, to form, for example, columnar thermal barriers on aerospace turbine or stationary turbine components, to form environmental barriers on ceramic-ceramic composite components, or to form functional layers in solid electrolyte fuel cell devices, to name just a few applications.
[0101] The wire and the thermal spraying device according to the invention are most particularly advantageous for forming columnar structured coatings and nanostructured coatings by spraying submicron particles contained in the wire. However, they avoid the disadvantages of the SPS or SPPS methods. "Columnar structures" are particularly described in the doctoral thesis of Benjamin Bernard, which deals with thermal barriers formed by suspension plasma spraying, which can be consulted at the following website: http: / / docnum.univ-lorraine.fr / public / DDOC_T_2016_0212_BERNARD.pdf.
[0102] Another advantage of the invention is that thermal spraying can be used to produce hybrid coatings (that is to say coatings comprising different materials) from wires comprising particles having different physicochemical properties.
[0103] The creation of the hybrid coating can be achieved using known thermal spraying techniques.
[0104] Hybrid coatings may be obtained from wires containing particles of ceramic oxide material and metal particles.
[0105] The invention can in particular combine different materials which, due to their different sizes or densities, are difficult to combine using other methods. This is particularly a major problem for thermal spraying of suspensions or dry powders which require co-injection during thermal spraying. BRIEF DESCRIPTION OF THE DRAWINGS
[0106] Other features and advantages of the present invention will become more apparent upon reading the following detailed description and examining the accompanying drawings, in which:
[0107] -[ Figure 1 ] Figure 1Schematically illustrating a thermal spraying device according to the present invention;
[0108] -[ Figure 2 ] Figure 2 Schematically shows a cross section of a wire according to the invention;
[0109] -[ Figure 3 ] Figure 3 The device for evaluating flexibility in the embodiment is schematically shown.
[0110] The same reference numbers are used throughout the various drawings to refer to the same or similar elements. DETAILED DESCRIPTION
[0111] definition
[0112] The "equivalent outer diameter" of a wire is the diameter of a disk having the same surface area as the cross-section of the wire at mid-length.
[0113] On the cumulative particle size distribution curve of the size of the particles of the particle assembly, the particle sizes corresponding to percentages equal to 10%, 50% and 90% by number are respectively referred to as the 10th percentile (denoted as D 10 ), the 50th percentile (denoted as D 50 ) and the 90th percentile (denoted as D 90 ), the particle sizes are classified in increasing order. According to this definition, the size of 10% of the particles in the particle assembly by number is therefore smaller than D 10 , 90% of the particles by number have a size greater than or equal to D 10 A particle size distribution curve can be created using a laser particle size analyzer. A SYSMEX FPIA3000 device can be advantageously used to obtain such a curve.
[0114] The 50th percentile of the particle aggregate D 50 The median particle size is called the “median particle size.” Therefore, the median particle size divides the particles of the particle assembly into a first population and a second population of equal numbers, and these first population and second population only contain particles with a size greater than or equal to the median particle size, or particles with a size less than the median particle size, respectively.
[0115] The percentiles of the sizes of the inorganic particles of the wire are the percentiles measured in the powder of the inorganic particles used to make the wire. They can be estimated from the wire by removing the binder from the wire by calcination, thereby eliminating the organic components and recovering the inorganic particles. If the inorganic particles can be oxidized and are easily damaged by the binder elimination temperature, the elimination of the binder is preferably carried out in a neutral atmosphere, for example in argon. The particle size distribution of the inorganic particles extracted by removing the binder can then be measured by volume measurement, for example by laser granulometry. From the volume of the wire, core or sheath, the volume distribution of the particles can be easily calculated, the size of which can be measured before and after removing the sheath of the wire, for example using a micrometer or calipers.
[0116] After drying for one hour at 110°C, a percentage measurement based on the "dry mass" of the thread can be made on a 100 g thread sample.
[0117] When calculating the volume percentage based on a wire, core or sheath, the volume of the wire, core or sheath is the volume defined by the outer surface of the wire, core or sheath.
[0118] The lubricant content by volume can be estimated from the amount of lubricant introduced into the starting charge during manufacture.The lubricant can be liquid or solid (graphite, BN, etc.).
[0119] The concept of "colorant pigment" is well known to the person skilled in the art. Pigments are powders which are colored during the production process of the line. Colorant pigments are usually in the form of powders with a median particle size of less than 1 micrometer. Colorant pigments can in particular be "oxide pigments", that is to say pigments consisting of oxides.
[0120] By "inorganic" particles are meant particles made of non-organic materials (that is, materials that do not contain a hydrocarbon chain as one of their main components). This family of materials includes metals, glasses and ceramics, as well as composite materials made of metals, glasses or ceramics. Preferably, the inorganic particles do not contain a hydrocarbon chain.
[0121] Materials that are neither metallic nor organic are referred to as "ceramics", for example materials selected from oxides, nitrides, carbides and chlorides. Ceramic materials include in particular glasses, cermets and glass ceramics. In the context of the present invention, diamond, graphite, graphene, and carbides of metals or metalloids are considered ceramic materials.
[0122] By "cermet" is meant a material containing at least two phases, at least one phase being a ceramic and at least another phase being a metal.
[0123] The term "brittle" defines a material whose domain of plastic deformation under load before fracture is less than 5%, preferably less than 1%, and preferably substantially zero, of the domain of elastic deformation. In other words, the width of the range of stress loads that results in plastic deformation without fracture is less than 5%, preferably less than 1%, of the width of the range of stress loads that results in elastic deformation.
[0124] Those components that are not desired in the wire are called "impurities", i.e. components other than inorganic particles, polymer binder, sheathing polymer and optional lubricant. Solvent residues are not considered as impurities. Impurities can include impurities present in the raw material source, but can also include residues of additives used in the manufacturing process of the wire, such as plasticizer residues.
[0125] The "ash content" of the wire corresponds to the residue left after the combustion of the matrix of the sheath and the core of the wire. It can be determined by calcination according to standard NF T30-012, by measuring the difference between the mass produced by calcination at a temperature of 450°C and the mass produced by calcination at a temperature of 950°C. The temperature of 450°C allows all the organic constituents to be decomposed and the temperature of 950°C allows any residues that could interfere with the melting of the inorganic particles to evaporate. The calcination needs to be sufficient to extract substantially all the organic constituents from the wire. Preferably the calcination is carried out for a sufficient duration so that said extraction is substantially complete. The calcination time is therefore adjusted to suit the size of the wire sample to be analysed.
[0126] The "volume content of mineral material" is measured by dividing the volume of the mineral material by the volume of the core of the thread. The volume of the core of the thread can be measured geometrically according to techniques well known to those skilled in the art. The volume of the mineral material is determined using the Archimedean method by weighing the mineral material extracted from the core of the thread after removal of the binder.
[0127] The percentages are determined "solvent exclusive" when the basis for calculating the percentage does not take into account any solvent that may be present. In particular, the solvent is preferably water, whereupon the volume percentages are measured by dividing the volume of the relevant component by the volume of the dry substrate (i.e., without taking into account any water that may be present), in particular the volume percentage of the inorganic particles, polymer binder, matrix lubricant, sheathing polymer or sheathing lubricant. The substrate may in particular be:
[0128] - core, in the case of inorganic particles,
[0129] -matrix, in the case of polymer binders and matrix lubricants,
[0130] - Jacketing, in the case of jacketing polymers and jacketing adhesives.
[0131] In order to exclude water, these percentages may be measured after complete drying.
[0132] In this specification, the qualifiers “upstream” and “downstream” are used according to the flow direction along the “flow axis” or “axis of flow” of the plasma generating gas flow or the flame gas flow.
[0133] The expression "based on" generally means that the corresponding amount is greater than 50% by mass.
[0134] A “transverse plane” is a plane perpendicular to the axis X.
[0135] A “radial plane” is a plane containing the axis X.
[0136] For the sake of clarity, a distinction is made between the "polymer binder" of the core of the wire and the "sheath polymer" of the sheath. The polymer binder and the sheath polymer may be the same or different.
[0137] Also for the sake of clarity, a distinction is made between a "matrix" adhesive and a "sheath" adhesive. These adhesives may be the same or different.
[0138] The terms "including," "comprising," "containing," and "having" are to be interpreted broadly and without limitation.
[0139] Detailed description
[0140] Spraying device
[0141] Figure 1 A thermal spraying device 10 according to the invention is schematically shown, comprising a torch 12 and a line 15 according to the invention for supplying inorganic particles to the torch.
[0142] The torch may in particular be a multi-cathode torch allowing axial injection, a flame torch, preferably a high velocity oxygen fuel (or HVOF) or high velocity air fuel (or HVAF) type torch, or a conventional wire flame torch, or a HVOF wire type torch or a HVAF wire type torch.
[0143] In conventional manner, the torch 12 comprises one or more plasma generators 13 or combustion gas generators 13 (in the case of a flame torch) and an injection device 14 for injecting a wire 15 along an injection axis I through an injection orifice 4 into a plasma flow 16 or flame generated in a chamber 17 upstream of a spray nozzle or jet nozzle 21 of the torch.
[0144] The axis of the plasma stream or flame is referred to as the "axis X".
[0145] In a radial plane containing the axis X and passing through the center of the injection orifice, the projection of the injection axis I forms an angle θ with the axis X. The angle θ is preferably greater than 60°, greater than 70°, greater than 80°, preferably greater than 85°. Preferably, the axis X is contained in the radial plane (preferably a radial plane that completely coincides with the axis X).
[0146] Wire
[0147] Figure 2 Schematically shown is a cross section of a wire 15 according to the invention. In particular, a core 18 and a sheath 20 surrounding the core can be discerned.
[0148] The wire preferably has a cross section that is constant over the entire length of the wire.The wire preferably has a circular cross section and preferably has an equivalent outer diameter greater than 1.5 mm, preferably greater than 2 mm and / or less than 3.3 mm, preferably less than 3.2 mm, preferably an equivalent outer diameter of 3 mm.
[0149] The wire is preferably wound on a spool, preferably packaged in the form of a spool that can be easily manipulated and unwound for feeding into a spraying device.
[0150] Preferably, the wire does not contain metal salts or hydroxides, for example any aluminium hydroxide (boehmite) which forms a gel during the preparation of the paste, nor any ammonium acetate. This is because the inventors have found that these ingredients mentioned in the prior art have a negative impact. In particular, the formation of inorganic gels (e.g. due to the use of aluminium hydroxide) causes the inorganic particles to aggregate together during the spraying process, which means that not all individual fine particles can be released, which is therefore not conducive to obtaining a finely structured layer. These ingredients also lead to a reduced flexibility of the wire in which the median particle size of the inorganic particles is less than 10 microns.
[0151] core
[0152] The core 18 in the form of a wire, preferably with a cross section that remains constant over the entire length of the wire, preferably has a circular cross section. The equivalent outer diameter of the cross section is preferably greater than 2 mm, and / or preferably less than 3.2 mm.
[0153] The core comprises an assembly of inorganic particles 22 which are intended to be melted in a plasma stream or flame into the form of droplets and then sprayed onto a substrate to form a coating on the substrate.
[0154] These inorganic particles preferably account for more than 40%, preferably more than 50%, preferably more than 55% and / or less than 80%, preferably less than 75%, preferably less than 70%, preferably less than 65% of the volume of the core of the wire. A volume content of inorganic particles less than 40% increases the energy consumption required to decompose the organic components of the binder matrix and the sheath during spraying. A volume content of inorganic particles greater than 80% is detrimental to the flexibility of the wire.
[0155] The median particle size D of the inorganic particle aggregate 50 Less than 10 microns. This very low median particle size is intended to allow for coatings with a very fine structure.
[0156] The median particle size D of the inorganic particle aggregate 50 Preferably less than 5 microns and preferably greater than 0.1 microns.
[0157] The median particle size of the inorganic particle assembly is preferably between 1 micrometer and 5 micrometers to obtain a dense coating for providing mechanical and / or chemical protection.
[0158] The median particle size of the inorganic particle assembly is preferably between 0.2 micrometers and 0.5 micrometers, in order to obtain a coating formed of columnar or "feather-like" layers with a more insulating microstructure, in particular in order to obtain a thermal barrier.
[0159] A median particle size greater than 0.1 micrometers may advantageously reduce safety issues during wire manufacturing.
[0160] Preferably, the equivalent outer diameter d (in micrometers) of the wire is equal to the median particle size D of the inorganic particles. 50 The ratio R (in micrometers) is between 200 and 20000, preferably greater than 500, preferably greater than 1000 and / or less than 10000, preferably less than 5000, preferably less than 2000. A ratio R between 200 and 1600 is particularly advantageous, in particular in the case of wires of high-speed flame or plasma torches for axial injection of feed material.
[0161] As a preference, (D 90 -D 10 ) / D 50 Greater than 1 and / or less than 1.8.
[0162] In one embodiment, for a median particle size of inorganic particles between 0.2 μm and 0.5 μm, the 10th percentile (D 10 ) is preferably greater than 50 nm, preferably greater than 100 nm, preferably greater than 150 nm, and the 90th percentile of the inorganic particle assembly (D 90 ) is preferably less than 1000nm, preferably less than 900nm, preferably less than 850nm.
[0163] In one embodiment, for a median particle size of inorganic particles between 1 μm and 5 μm, the 10th percentile (D 10 ) is preferably greater than 0.1 micron, preferably greater than 0.5 micron, and the 90th percentile of the inorganic particle assembly (D 90 ) is preferably less than 10 microns, preferably less than 8 microns.
[0164] The nature of the inorganic particles will be determined by the desired properties of the coating.
[0165] Preferably, the inorganic particles are made of a material which consists, by weight, of more than 80%, preferably more than 90%, preferably more than 95%, or even substantially 100%, of one or more of the following oxides, alone or in the form of a solid solution: Al2O3, SiO2, ZrO2, Cr2O3 and TiO2.
[0166] The inorganic particles may be made of non-oxide materials, in particular selected from:
[0167] - a metal oxide, preferably made of aluminum oxide, zirconium oxide, titanium oxide, chromium oxide, yttrium oxide or a combination of several of these oxides (for example mullite or spinel), and / or
[0168] - cermets based on carbides, such as carbides of chromium, tungsten, titanium, tantalum, zirconium, which are associated with a metal phase, and / or
[0169] - SiC-YAG composites, YAG stands for yttrium-aluminum garnet, capable of thermal spraying SiC-based compounds, and / or
[0170] - Ceramics, such as nitrides, borides and carbonitrides, may be associated with the metal phase in the form of cermets, and / or
[0171] - a refractory metal or a refractory metal alloy, preferably with a melting point above 2500K, and / or
[0172] - alloys of special metals, such as amorphous metals, quasicrystals or quasicrystal-like phases and, more generally, metal alloys that cannot be drawn.
[0173] Special metal alloys are generally alloys of metals, in particular alloys that undergo brittle mechanical fracture, such as amorphous metals or metallic glasses, quasicrystals or quasicrystal-like phases (ie, phases approximating quasicrystals), such as described in https: / / www.universalis.fr / encyclopedie / quasi-cristaux / 4-phases-approximantes-et-defauts / .
[0174] Preferably, the inorganic particles are selected from particles made of ceramics, particles made of metal alloys, particles made of amorphous metals, and particles made of quasicrystals or quasicrystal-like phases.
[0175] Inorganic particles made of carbides are particularly well suited to HVOF technology.
[0176] The inorganic particles are embedded, and preferably substantially uniformly dispersed, in a matrix 24 that binds the inorganic particles.
[0177] The matrix is essentially composed of organic material, so that the matrix can be reduced to the form of ash during spraying.
[0178] The volume content of the plasticizer may be greater than 1%, preferably greater than 4% and / or less than 10%, preferably less than 8%, in volume percentage based on the volume of the core or matrix excluding the solvent. The plasticizer may be any known plasticizer, such as phthalates, in particular BDP (butyl benzyl phthalate), or polyvinyl alcohol (referred to as PVA in its abbreviated form).
[0179] In a preferred embodiment, the complement to 100% of the polymer binder in the matrix (excluding impurities and solvent residues) comprises, preferably consists of, a lubricant, preferably glycerol. The lubricant may in particular constitute 10% to 20% of the volume of the core.
[0180] jacket
[0181] The sheath 20 contributes to the flexibility of the wire by enhancing its ability to withstand bending without damage. In particular, the sheath allows the wire to be wound without visible damage, and in particular without rupture or separation of its components. Thus, the sheath contributes to the toughness of the wire, which is required due to the small equivalent outer diameter of the wire, and imparts a surface finish to promote sliding, so that the wire can be passed more easily through the injection orifice of the torch, and to limit the wear caused to those parts of the torch that come into contact with the wire, in particular the injection orifice.
[0182] The sheath surrounds the core over the entire length of the wire.The sheath preferably has a constant thickness in a plane perpendicular to the length direction of the wire, preferably in any arbitrary plane perpendicular to the length direction of the wire.
[0183] Preferably, the ratio of the thickness of the sheath (in micrometers) to the equivalent outer diameter of the wire (in micrometers) is greater than 0.03 and less than 0.6, preferably greater than 0.05, or even greater than 0.1 and / or less than 0.5, or even less than 0.3, or even less than 0.2. A ratio between 0.05 and 0.5 is very particularly suitable when the inorganic particle assembly has a median particle size of less than 5 micrometers.
[0184] Preferably, the main component of the sheath is a polymer from the same family as the polymer binder of the matrix of the core of the thread, or even a polymer having the same chemical composition as the polymer binder of the matrix of the core of the thread, or even a polymer having the same empirical formula as the polymer binder of the matrix of the core of the thread. The crosslinking monomers forming the polymer of the sheath are preferably the same as the crosslinking monomers of the polymer binder.
[0185] The sheath polymer preferably comprises from 55% to 75%, preferably about 65%, of the volume of the sheath (excluding solvent).
[0186] Preferably, the sheath contains a lubricant called "sheath lubricant", preferably glycerol, preferably in an amount greater than 25% by volume based on the sheath (excluding solvents). The sheath lubricant contributes to the quality of the coating produced by coextrusion during its manufacture, limiting wear on those parts of the torch on which the wire slides and limiting the risk of buckling of the wire when injected into the plasma stream or flame, by facilitating sliding.
[0187] The complement up to 100% of the sheath polymer and the sheath lubricant preferably consists of organic impurities, in particular organic impurities resulting from organic additives such as plasticizers used to shape the sheath of the wire during production.
[0188] Typically, the composition of the matrix and the sheath is determined in such a way as to obtain a low ash content of the wire. The ash content resulting from the presence of the polymer binder used, the matrix lubricant, the sheath polymer, the sheath lubricant and the plasticizer is preferably less than 2.5%, preferably less than 2%, or even less than 1%, as a percentage by mass based on the mass of the wire. A person skilled in the art knows how to adjust the composition to reduce its ash content, and can do so by performing some simple tests.
[0189] Ash contents greater than 3% mean a high content of organic components and severe contamination of the torch. This leads to serious interruptions in the process and is a source of defects in coatings obtained by thermal spraying.
[0190] In particular, preferably, the sheath polymer and / or the polymer binder of the matrix, preferably the organic charge consisting of the sheath polymer and the polymer binder of the matrix, consists of a cellulose derivative for more than 80 mass %, more than 90 mass %, more than 95 mass %, preferably substantially 100 mass %, the percentages being by volume based on the sheath or the polymer binder, respectively (excluding solvent). Cellulose derivatives advantageously allow very low ash contents, typically less than 1 %, as a mass percentage based on the mass of the thread.
[0191] Preferably, the cellulose derivative is selected from cellulose ethers, preferably from methylcellulose (MC), ethylcellulose (EC), methylethylcellulose (MEC), hydroxymethylcellulose (HMC), hydroxyethylcellulose (HEC), methylhydroxyethylcellulose (MHEC), hydroxymethylethylcellulose (HMEC), hydroxypropylcellulose (HPC), hydroxypropylmethylcellulose (HPMC), hydroxypropylethylcellulose (HEPC), carboxymethylcellulose (CMC), and mixtures thereof. Preferably, the cellulose derivative is selected from hydroxyethylcellulose, in particular methylhydroxyethylcellulose, because this subfamily of cellulose has rheological properties that are very suitable for the manufacture of small diameter threads (wherein the median particle size of all inorganic particles is less than 10 microns).
[0192] The alkali content (especially sodium content) in the cellulose derivative is preferably less than 1%, calculated as a mass percentage based on the mass of the cellulose derivative. This feature can advantageously limit the ash content and long-term corrosion of the torch. Preferably, the cellulose derivative does not contain cellulose fibers or contains a small amount of cellulose fibers.
[0193] The wire according to the invention can be manufactured using any conventional method, in particular by coextrusion of a first paste for forming the core of the wire and a second paste for forming the sheath. A method of this type is described in particular in FR 1 443 142.
[0194] The method described in GB 1 151 091 A is particularly suitable, for example.
[0195] The flexibility of the wire can be easily adjusted by adjusting the amount of polymer binder in the core and its viscosity and / or the viscosity of the sheathing polymer.
[0196] application
[0197] The wire according to the invention is particularly suitable for plasma torches, in particular plasma torches with axial injection, especially multi-cathode plasma torches, also called “multi-chamber” torches.
[0198] The flexibility of the wire according to the invention allows it to be wound on a spool so that the wire can be unwound when forming the coating. Spraying can thus be substantially continuous. The sheath also ensures smooth contact with the injection orifice, thereby limiting wear of the injection orifice.
[0199] However, the wire is sufficiently rigid to allow substantially axial injection, preferably using a drive device offset upstream of the torch. Such axial injection promotes uniform heating of the inorganic particles, uniform distribution of the jet of inorganic particles in the injection nozzle, thereby limiting nozzle fouling and improving coating repeatability and quality.
[0200] The limited amount of liquid phase, in particular solvent, limits the energy consumed and maximizes the energy available for pyrolyzing the sheath and matrix and melting the inorganic particles.
[0201] The size of the inorganic particles is selected based on the spraying equipment and the desired microstructure of the coating.
[0202] From the moment the wire enters the chamber 17 of the torch, the following sequence of events occurs:
[0203] - The sheath and polymer binder are pyrolyzed;
[0204] - Individual inorganic particles are released without any aggregation effect;
[0205] - inorganic particles are rapidly entrained in the (flame or plasma) jet and completely or partially melted in flight,
[0206] - The at least partially molten inorganic particles impinge on the substrate and then solidify to form a coating.
[0207] In particular, this line can be used to produce:
[0208] - coatings providing mechanical or chemical protection, in particular protection against corrosion by chemicals, vapors, etching plasmas;
[0209] - Environmental or thermal barriers;
[0210] - Coatings with tribological functions, anti-wear coatings, electrical insulating coatings, or conductive coatings.
[0211] Preferably, the thickness of the coating is between 10 microns and 500 microns.
[0212] Example
[0213] To illustrate the present invention, the following non-limiting examples are given.
[0214] Example 1 was performed by extruding a first paste according to the teaching of JP2016156058.
[0215] For other embodiments, according to the teaching of GB 1 515 091, a first paste is produced from:
[0216] - a powder of alumina particles obtained by melt solidification, with a median particle size of 7.5 micrometers and a purity greater than 99.5%, and
[0217] - Methylhydroxyethylcellulose (polymer binder) with a viscosity of 50 mPa·s.
[0218] For methyl hydroxyethyl cellulose powder mixed with 2% by mass of demineralized water, use The viscometer measures the viscosity of methyl hydroxyethyl cellulose at 20°C.
[0219] The mass ratios of the components of the first paste are shown in Table 1 below.
[0220] Then, a second paste for forming the sheath was prepared. To this end, the same methylhydroxyethylcellulose as used for preparing the first paste was kneaded with a certain amount of water, glycerin and colorant pigment in the mass ratio shown in Table 1 below.
[0221] The first paste and the second paste were co-extruded in an extruder to obtain a 3 mm flexible wire precursor having a substantially circular cross section, an outer diameter of 3 mm and a sheath thickness of substantially 350 microns.
[0222] Drying of the wire precursor resulted in a residual water content of the wire of less than 5%. Residual moisture measurements showed values of approximately 3%. The wire was wound onto a spool having a diameter of 70 mm.
[0223] Diameter and thickness
[0224] Using Digital Tesa 0-30mm micrometer measures the outer diameter of the wire and the thickness of the sheath.
[0225] Flexibility Testing
[0226] For each example:
[0227] - Wrap a sample of at least 0.5 m of the wire to be tested around a cylindrical rod of 25 mm diameter to form continuous turns, such as Figure 3 This operation must not cause the line to break;
[0228] - Wrap a sample of at least 0.5 m of the wire to be tested around a cylindrical rod of 70 mm diameter to form continuous turns, such as Figure 3 The sheath of the wire shall not have cracks visible to the naked eye from the outside, nor shall it have internal cracks visible to the naked eye from the outside through color changes caused by the translucency of the sheath;
[0229] - A wire drive test is carried out on a sample of wire of at least 0.5 m, which consists in running a 2 kg roller with a diameter of 26 mm along the sample at a speed of 1 m / s. The wire is allowed to deform slightly and show a diameter variation of less than 15%, but no cracks visible to the naked eye from the outside shall be present.
[0230] If the wire passes these 3 tests, then its flexibility is acceptable. If it fails at least one of the three tests, then its flexibility is unacceptable.
[0231] Ash content
[0232] The ash content is determined by (m0-m1) / m0, where m0 and m1 are the masses of a wire of 3 cm sample length after calcination in a furnace at 450°C and 950°C in air for 1 hour, respectively.
[0233] Ratio R
[0234] The ratio R is the equivalent outer diameter of the wire (in micrometers) divided by the median diameter of the inorganic particles (D 50 ) (in microns) ratio.
[0235] Enthalpy change
[0236] Based on the formulation of each example, use The software calculated the enthalpy change associated with the decomposition of the organic components of the wire at 2300K for each example, taking into account the following:
[0237] - between the orifice through which the plasma stream or flame leaves the generator and the spray nozzle (or injection nozzle), the injection line is injected upstream of the flame or plasma stream;
[0238] - In the case of a high-speed plasma torch, a neutral atmosphere (that is, an atmosphere without oxygen and without hydrogen) and C x H y Decomposition products produced by linear decomposition of type;
[0239] - in the case of a high velocity oxygen flame (HVOF type) torch, oxidizing atmosphere and direct decomposition into CO2 and H2O;
[0240] - After drying, the residual water in the thread was measured to be 3%.
[0241] When determining the amount and nature of the organic product of the thread, the addition of organic compounds caused by the possible presence of the sheath is taken into account.
[0242] In Table 1 below, the enthalpy changes are given in kJ / mol alumina.
[0243] It is considered to be particularly advantageous if the enthalpy change in the neutral atmosphere is as low as possible, in particular less than or equal to 1000 kJ / mol of aluminum oxide, expressed in absolute terms.
[0244] It is considered to be particularly advantageous when the enthalpy change in the oxidizing atmosphere is less than +1000 kJ / mol of alumina.
[0245] The amount of inorganic particles is given as volume percent based on the volume of the core of the wire, without taking into account the solvent.
[0246] Example 1 (comparative example) was carried out according to the teaching of JP2016156058 without a sheath. Example 3 (comparative example) was carried out according to the teaching of GB 1 151 091, but using finer inorganic particles. Example 4* and Example 5* are examples according to the present invention.
[0247] [Table 1]
[0248]
[0249] MHEC: methyl hydroxyethyl cellulose; ND: not determined; NA: not applicable
[0250] As is now clearly visible, the invention provides a wire which, due to its flexibility, can advantageously be introduced continuously into the center of a flame or plasma substantially along the axis of a torch. The inorganic particles are properly dispersed during spraying. The thermal decomposition characteristics of the wire, in particular its very low enthalpy change at 2300 K, make it possible to obtain, with limited energy consumption, a coating which advantageously exhibits a controlled roughness and is free of defects.
[0251] Of course, the invention is not limited to the embodiments and implementations described, which are provided by way of illustrative and non-limiting examples.
Claims
1. A wire for use as feedstock for a thermal spraying torch to produce a coating, the wire having an equivalent outer diameter (d) of 1 mm to 3.5 mm and consisting of a core (18) in the form of a wire and a sheath (20) covering the core along its entire length, The core is composed of: -Median particle size (D 50 ) an aggregate of inorganic particles (22) smaller than 10 microns, said inorganic particles occupying more than 40% and less than 80% of the volume of said core, said inorganic particles being particles of one or more metal oxides, and / or particles of carbide-based cermets, and / or inorganic particles of SiC-YAG, and / or particles containing or made of ceramic materials, and / or particles made of one or more metals or metal alloys having a melting point higher than 2500K, and / or particles made of special metal alloys; and - a matrix (24) for binding the inorganic particles, the matrix comprising: - a polymer binder, more than 80% by mass of which consists of a cellulose derivative, and -optionally, a base lubricant, The polymer binder and the matrix lubricant together comprise greater than 90% by volume of the matrix, The sheath (20) has a thickness of 50 to 500 microns and comprises: - a polymer referred to as "sheath polymer", more than 80% by mass of said sheath polymer consisting of a cellulose derivative, and - preferably a lubricant known as "sheath lubricant", The sheath polymer and the sheath lubricant together comprise greater than 90% of the volume of the sheath, The volume percentages are determined without taking into account any solvent residues that may be present. The median particle size of an aggregate of particles is the 50th percentile of the aggregate of particles corresponding to 50% by number on a cumulative particle size distribution curve of the sizes of the particles of the aggregate of particles, determined using a laser particle size analyzer, and the sizes of the particles are arranged in increasing order.
2. The thread according to the preceding claim, wherein The ash content of the wire is less than 5%, the ash content being determined by (m0-m1) / m0, m0 and m1 being the mass of a 3 cm sample length of the wire after calcination in a furnace at 450°C and 950°C in air for 1 hour, respectively.
3. The thread according to the preceding claim, wherein The matrix and the sheath of the wire have an ash content of less than 1%.
4. A thread as claimed in any one of the preceding claims, wherein The equivalent outer diameter (d) of the wire in micrometers is proportional to the median particle size (D 50 ) ratio (R) is 200 to 20000.
5. The thread according to the immediately preceding claim, wherein The ratio (R) is 200 to 2,000.
6. A thread as claimed in any one of the preceding claims, wherein The median particle size D of the aggregate of the inorganic particles 50 Less than 5 microns.
7. A thread as claimed in any one of the preceding claims, wherein The core polymer binder and / or the sheath polymer has a viscosity of 30 to 300 mPa·s at 20°C.
8. A thread as claimed in any one of the preceding claims, wherein The sheath contains a sheath lubricant, and the content of the sheath lubricant is greater than 10% and less than 50% by volume percentage based on the volume of the sheath, excluding possible solvents.
9. The thread as claimed in any one of the preceding claims, wherein The inorganic particles are selected from: - particles of aluminum oxide, zirconium oxide, titanium oxide, chromium oxide, yttrium oxide, or a combination of several of these oxides, and / or - particles of a cermet containing more than 50% by mass of carbides selected from the group consisting of chromium carbides and / or tungsten carbides and / or titanium carbides and / or tantalum carbides and / or zirconium carbides and / or niobium carbides, and / or - particles of a ceramic material in the form of a nitride, boride or carbonitride, optionally associated with a metallic phase in the form of a cermet, and / or - particles of brittle material, and / or - Particles of an amorphous metal alloy, or a quasicrystal or a quasicrystal-like phase, or a non-drawable metal alloy.
10. The thread as claimed in any one of the preceding claims, wherein The thickness of the sheath is greater than 200 microns and less than 400 microns.
11. The thread as claimed in any one of the preceding claims, wherein The polymer binder and the jacket polymer comprise the same polymer.
12. An assembly comprising a spool of diameter less than 500 mm and a wire as claimed in any preceding claim, the wire being wound around the spool.
13. A thermal spraying device comprising: - a torch (12) comprising a plasma jet generator or a flame generator (13) and an injection device (14); and - a wire (15) according to any one of claims 1 to 11, arranged in such a way that it can be injected by the injection device into the plasma flow or the flame generated by the generator, The torch is capable of at least partially melting the inorganic particles and ejecting the at least partially melted inorganic particles at more than 150 m / s.
14. Thermal spraying device according to the immediately preceding claim, wherein: The injection device is arranged in such a way that the line is injected along an injection axis (I), wherein the injection axis (I) extends in a plane passing through the axis (X) of the plasma flow or the flame and forms an angle θ with a plane perpendicular to the axis (X), the absolute value of which is greater than 60°, preferably greater than 80°.
15. Thermal spraying device according to any of the two preceding claims, wherein: The injection device is arranged in such a way that the wire is injected into the spray nozzle of the torch or upstream of the injection nozzle of the torch.
Citation Information
Patent Citations
cord for torch spray coating
FR1443142A
Cord for Coating by Blowpipe Projection.
GB1151091A
Instrument for indicating the depths and durations of decompression stops required during underwater submersions
GB1515091A
Plasma spray apparatus and plasma spray method
JP2016156058A
Flexible welding rod having organically bound core and protective sheath
US3701444A